Degradation Characteristics and Mechanisms of Steel Fiber-Reinforced Concrete Linings in Subsea Tunnels: Insights from Accelerated Erosion Tests with Applied Electric Fields - Longhai Wei; Jiguo Liu; Heng Shu; Qinglong Cui; Wenbo Peng; Huimin Gong; Yiguo Xue; Min Han (Journal of Marine Science and Engineering)
Understanding the long-term durability and degradation mechanisms of steel fiber-reinforced concrete (SFRC) linings in subsea tunnels is critical for ensuring structural safety, cost effectiveness, and sustainability. This study investigated the degradation characteristics of SFRC with varying fiber contents (0%, 0.35%, 0.55%, and 0.75%) and different acceleration durations, using the applied electric field acceleration method and X-ray CT tests. The experimental results revealed the characteristics of the surface crack distribution and evolution patterns in the SFRC specimens. Furthermore, the similarity between the non-uniform corrosion patterns observed in regard to accelerated corrosion under the applied electric fields and those occurring due to natural degradation was verified. The pore structure characteristics and internal crack development of the SFRC specimens were compared. The study found that the degradation process of the specimens was closely related to the fiber content. The incorporation of steel fibers altered the crack initiation and propagation modes, leading to a more scattered crack distribution. The accelerated corrosion method, employing an applied electric field, successfully simulated the non-uniform corrosion process of reinforcement in SFRC linings in subsea tunnels under natural conditions. Under the influence of a unidirectional chloride ingress source, the pronounced accumulation of corrosion products was observed only on the side of the reinforcement exposed to chloride penetration. This method effectively visualized the chloride penetration path and its impact on reinforcement corrosion, providing valuable insights for the anti-corrosion design of SFRC linings in subsea tunnels.